Pendampingan Pembuatan Teknologi Tepat Guna dalam Pengelolaan Lingkungan: Perspektif Hukum Lingkungan dan Legalitas di Indonesia: Penelitian - Hifni, Mohammad; Adhitya; Tiara Kurnia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Assistance in the development of appropriate technology (AT) in environmental management is a strategic effort to encourage community participation in maintaining ecosystem sustainability while improving quality of life. Simple, affordable, and locally appropriate technologies have proven effective in addressing environmental issues such as waste management, renewable energy utilization, and water conservation. However, the success of TTG implementation depends not only on technical aspects but also on compliance with Indonesia’s environmental legal framework and applicable regulations. Through an environmental law approach, every technological innovation must adhere to the principles of precaution, sustainability, and the right to a good and healthy environment as stipulated in Law No. 32 of 2009 on Environmental Protection and Management. This research/assistance aims to analyze the role of law in guiding the legality of TTG so that it does not conflict with regulations, as well as providing legal protection for users and developers. The results of the study show that TTG assistance integrated with legal aspects not only improves the effectiveness of environmental management but also provides legal certainty and encourages sustainable innovation.